2014
DOI: 10.1063/1.4895925
|View full text |Cite
|
Sign up to set email alerts
|

Thin film cadmium telluride charged particle sensors for large area neutron detectors

Abstract: Thin film semiconductor neutron detectors are an attractive candidate to replace 3 He neutron detectors, due to the possibility of low cost manufacturing and the potential for large areas. Polycrystalline CdTe is found to be an excellent material for thin film charged particle detectorsan integral component of a thin film neutron detector. The devices presented here are characterized in terms of their response to alpha and gamma radiation. Individual alpha particles are detected with an intrinsic efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The peak broadening (Figure 5a) can be due to various factors, such as the attenuation of alpha particles by the air and the top electrode, charge trapping in semiconductor, and electronic noise. [ 40 ] Next, the diode was exposed to thermal neutrons using a 252 Cf source (Figure S20, Supporting Information). The response of the diode is shown in Figure S21a, Supporting Information.…”
Section: Alpha and Neutron Sensingmentioning
confidence: 99%
“…The peak broadening (Figure 5a) can be due to various factors, such as the attenuation of alpha particles by the air and the top electrode, charge trapping in semiconductor, and electronic noise. [ 40 ] Next, the diode was exposed to thermal neutrons using a 252 Cf source (Figure S20, Supporting Information). The response of the diode is shown in Figure S21a, Supporting Information.…”
Section: Alpha and Neutron Sensingmentioning
confidence: 99%
“…Figure shows the basic CdS/CdTe diode structure [ 26 ] where an N‐type CdS layer and a lightly P‐type CdTe layer are sequentially deposited on a glass substrate to form a P‐N junction. Indium tin oxide (ITO) and Cu/Au are used as bottom and top contacts, respectively.…”
Section: Basic Cds/cdte Diode and Integration With Poly‐si Tftsmentioning
confidence: 99%
“…[ 22–25 ] Poly‐Si is also stable at temperatures higher than 400 °C, which enables the use of poly‐Si‐based circuits in systems that require moderate growth temperatures, such as CdTe, which is usually deposited at 450 °C. [ 18,26 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al reported multilayers of CdTe quantum dots as formaldehyde gases sensors. [10] Filipenko et al and Murphy et al also reported the use of single crystal and thin films CdTe as particle detectors for -particles, single electrons, and thermal neutrons [11,12]. An additional advantage of thin film CdTe is that it can be deposited using a wide variety of methods including sputtering, close-spaced sublimation, pulsed laser deposition, physical vapor deposition, among others [2,13,14].…”
Section: Introductionmentioning
confidence: 99%